LITERATURE REVIEW: KAITAN ANTARA KINERJA KEUANGAN DAN PENGHINDARAN PAJAK DI INDUSTRI KEUANGAN INDONESIA - Iyaza Zumariz; Sofie Yunida Putri (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to analyze the influence of financial performance and avoidance practices in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. This research employs a qualitative method using a literature study to various articles from Sinta indexed journals, financial reports, and other secondary data. The findings suggest a significant relatedness between financial performance and the tendency to engage in tax avoidance. Companies with strong financial performance may have more resources to pursue aggressive tax planning, while financially pressured firms may also seek tax avoidance strategies to preserve cash flow. This study is expected to contribute theoretically to tax literature and provide insights for policymakers in designing more effective tax supervision policies in the financial sector.